(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper identifies the absence of both sub-continentally oriented histories which knit together the land and sea trades, and convincing explanations of the persistence of the Indo-Central Asian trade (for example) despite the growing Indo-European trade from the seventeenth-century. The customs-union model usefully approximates this trading-situation (i.e. the Europeans were given a privileged trading position by the Mughals vis-à-vis the Central Asians). It is used to structure the investigation and provide suitable explanatory hypotheses, as it suggests the separation of the likely creative and divertive effects of such privileged relations. Two tradable (and related industries) are examined. The textile-industry demonstrates the possibility for trade-creation (i.e. due to substitution between otherwise regionally-specialized production-centres as in Gujarat, and the utilisation of spare capacity as in Bengal); it is not, however, possible to comment on the extent to which trade-creation took place. The horse-trade persisted because of limited trade-diversion. This was in turn the consequence of the absence of a European supply of horses, on the one hand, and the continued/unchanging geographical comparative advantage and demand conditions in the Mughal Empire, on the other.